The marginalization of Africa in world trade - Bora, Saswati; Bouët, Antoine; Roy, Devesh (International Food Policy Research Institute, 2007)
In recent years, trade in Africa has assumed greater importance as a means of alleviating poverty, especially since the initiation of the Doha Round for development. At the same time, skepticism regarding the effectiveness of foreign aid has grown (Easterly 2006). Trade and aid have often been viewed as interchangeable, but “aid for trade” has recently gained prominence, with the result that the two factors are more often treated as complementary. Proponents of “aid for trade” argue that the capacity of developing countries to take advantage of any gains in market access through the Doha Round is hampered by a plethora of supply-side bottlenecks and costs, administrative constraints, and poor institutions. Aid for trade, thus, refers to additional aid to tackle trade-related constraints and adjustment costs in developing countries (Evenett 2005).1 Views differ as to what this package should entail, but many developing countries are in favor of building supplycapacity and trade-related infrastructure (IATP 2006).